Neonatal Cerebral Infarction and Neuromotor Dysfunction - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Twenty-two children with cerebral infarction on neonatal MRI were examined neurologically at school age in a study at Imperial College School of Medicine, Hammersmith, London, UK.